From wastewater to resource - Petrik, L. F.; Ngo, H.H.; Varjani, S.; Osseweijer, P.; Xevgenos, D.; Loosdrecht, M. van; Smol, M.; Yang, X.; Mateo-Sagasta, Javier (Elsevier, 2022)
Eighty percent of wastewater is left untreated or not reused, exacerbating the water quality challenge, especially in vulnerable communities. This Voices asks: how can we improve wastewater management and convert wastewater into a resource?